THE EFFECTS OF SOCIAL MEDIA MARKETING, STORE ENVIRONMENT, AND SALES PROMOTION ON CONSUMER PURCHASE DECISION AT PT MEGAMAS PLAZA BANGUNAN, MEDAN - Alfonsius Alfonsius; Micho Christian (Jurnal Ekonomi, 2023)
This research is purposed to test and analyze the effects of social media marketing, store environment, and sales promotion on consumer purchase decision at PT Megamas Plaza Bangunan (Home Smart), Medan. The result shows that the Adjusted R Square value is 0.631 which means that 63.1% of consumer purchase decision is jointly influenced by the variables described in the model, while the rest is influenced by factors outside the model. Partially, each independent variable, which is social media marketing, store environment, and sales promotion, has positive significant effect.